Development of general biomass allometric equations for Tectona grandis Linn.f. and Eucalyptus camaldulensis Dehnh. plantations in Thailand - Ounban, Waraporn; Puangchit, Ladawan; Diloksumpun, Sapit (Agriculture and Natural Resources, 2016)
Some common, general biomass allometric equations were developed and tested for estimating the stem and aboveground biomass (AGB) of Tectona grandis and Eucalyptus camaldulensis plantations. In total, 84 datasets for T. grandis and 94 datasets for E. camaldulensis were gathered from published papers. The general allometric equations were then developed and the slopes and elevations were tested using ANCOVA. Spacing of 2 m x 4 m, 2 m x 8 m, 3 m x 3 m and 4 m x 4 m for T. grandis and 2 m x 3 m, 2 m x 4 m, 2 m x 8 m and 3 m x 3 m for E. camaldulensis were used as control factors. The results confirmed that diameter at breast height (D) and total height (H) were the best parameters for biomass estimation, of which the simple combination D2H produced the best estimation. The general allometric equations which gave the best fit (p < 0.01) for the estimation of T. grandis was AGB = 0.045(D2H)0.921 and for E. camaldulensis was AGB = 0.033(D2H)0.959. Comparison of the measured and estimated datasets showed no statistically significant differences (p > 0.05). The range of D and H was 4.4-41.2 cm and 5.5 -31.0 m, respectively, for T. grandis and 0.5-19.8 cm and 1.7-26.0 m, respectively, for E. camaldulensis.